Toward critical multimodality : theory, research, and practice in transformative educational spaces - Silvestri, Katarina N.; Barrett, Nichole; Nyachae, Tiffany M. (Contemporary perspectives on semiotics in education: signs, meanings, and multimodality, 2023)
"This edited volume seeks to answer the question, "What does it mean to be a critical multimodal scholar in educational spaces?" Toward Critical Multimodality highlights how choices made throughout multimodal design and research processes are critically-oriented and inextricably linked to power. We show how social semiotics and multimodality inform engagement with criticality in educational spaces through questioning dominant narratives (e.g., white, cisheteropatriarchal, ableist, classist perspectives), exploring relationships between selves and space, problematizing and reimagining educational practices, and dreaming of educational futures that are just, anti-oppressive, and with room for all to thrive while learning. These chapters demonstrate how studying multiple modalities in interaction (e.g., image, writing, color, spatial layout, gaze, proxemics, gestures) can reveal how power operates, provide students with opportunities to explore themselves and their identities with respect to power, and provide a vehicle for scholars to disrupt and transform oppressive educational practices. Furthermore, multiple chapters show alternative ways to display, construct and share knowledge as transformative pedagogical practice in learning environments. We reframe social semiotics and multimodality as an integral part of decentering dominant ideas of power and what "counts" as purposeful meaning making by highlighting how criticality and multimodality integrate theoretically and methodologically"--